Queerbaiting and fandom : teasing fans through homoerotic possibilities - Brennan, Joseph, 1986- (Fandom & culture., 2019)
"In 2007, while giving a book talk, Harry Potter author J.K. Rowling revealed an interesting fact about beloved character Albus Dumbledore's love life. "Dumbledore is gay, actually," she said as the audience erupted in cheers. She added: "I would have told you earlier if I knew it would make you so happy." Though most fans initially praised the announcement, LGBTQ fans in particular questioned why the author chose to make it informally, while never actually writing explicitly gay characters into the storylines. As it turns out, this type of bait-and-switch is fairly common between fans and creators; there's even a term for it: "queerbaiting." In this first comprehensive examination of queerbaiting, fan studies scholar Joseph Brennan and his contributors examine cases like Rowling's to shed light on the exploitative industry practice of teasing homoerotic possibilities that, while hinted at, never materialize in the program narratives. Looking at everything from popular TV series to video games to children's programs, and more, these essayists--some of the biggest names in the emerging field of fan studies--explore the consequences of the misleading practice, both for fans and creators. The result is a first-of-its-kind collection that is sure to appeal equally to fan, queer, and media studies students and scholars"--